Cordocentrism of Ivan Prokopenka`s and Grigory Skovorody`s pedagogical outlook - Vorozhbit-Horbatiuk, V.; Boiarska-Khomenko, A.; Sobchenko, T. (New Collegium, 2022)
The study of the unified basis of the pedagogical worldview of Ivan Prokopenko and Grigory Skovoroda is relevant in the conditions of martial law in Ukraine and is due to the tragic events that the entire civilized world lives. The article is aimed at revealing the cordocentric basis of the pedagogical worldview of these educators and teachers. To achieve the goal, comparative historical and systemically structural methods were used to characterize the pedagogical worldview of each educator, to reveal the basic concept of publication. Methods specifically search – analysis, synthesis of generalization of historical facts – used to characterize cordocentrism through the prism of the pedagogical work of Grigory Skovorolda and pedagogical achievements of Ivan Prokopenko. The retrospective method was used to creatively interpret the results of the research. In the article, the results of the study are presented in accordance with synergistic, systemic, axiological approaches. The authors emphasized n6a because cordocentrism can be a synthesizing feature of the pedagogical worldview of these enlighteners. They formed pedagogical views on the basis of the idea of the naturalness of work, understanding of gratitude as the basis of worldview ethics and quality, unity of secular and religious ethics, life practice of cordial attitude to a person, mental attitude to the interlocutor, sincerity even in the most intimate senses and search for oneself, self-knowledge. The authors highlighted the significance of the phenomenon, Skovorodinovsky person, Skovorodinovsky intelligentst. In demand, in the opinion of the authors, are the practices of deep knowledge of themselves for the restoration and establishment of peace in Ukraine, the development of the best mentality traits for the continuous civilizational progress of Ukrainians, axiological understanding of the will, recognition of self-worth and psycho-emotional dependence on the native land, preservation of the memory of generations, diligence as signs of spiritual harmony and sensual residence of all things. These cordocentric imperatives combine the pedagogical worldviews of the great enlightener Grigory Skovoroda and the outstanding academician Ivan Prokopenko. These cordocentric imperatives combine the pedagogical worldviews of the great enlightener Grigory Skovoroda and the outstanding academician Ivan Prokopenko.